Local recurrence in sigmoid cancer is a hidden problem, could CT prognostic factors be of value in their prevention? A multi-centre study of 414 patients. Issue 8 (August 2021) - Day, Nigel; D'Souza, Nigel; Shaw, Annabel; Lord, Amy; Abulafi, Muti; Moran, Brendan; Tekkis, Paris; Brown, Gina
Abstract: Introduction: The incidence and patterns of local recurrence of colon cancer are not well reported. The aim of this study was to investigate the contemporary rates and patterns of local recurrence after sigmoid cancer resection, comparing pre and post-operative biomarkers in predicting local disease recurrence. Materials and methods: A multi-centre, retrospective analysis of 414 patients undergoing resectional surgery for sigmoid colon cancer was conducted. Multivariable Cox Proportional Hazard models were created to identify variables associated with local disease recurrence. Patterns of recurrence and prognostic significance of pre and post-operative variables were identified. Results: In 414 patients, the local recurrence rate was 12.6%. The R1/R2 rate was 2.4%. Local recurrence occurred most commonly within the peri-anastomotic region (50%), followed by the peritoneum (33%). On multivariate analysis, local recurrence was predicted by pathological T stage (HR 1.15) and R1 resection (HR 2.95), but also computerised tomography (CT) identified tumour deposits (HR 2.40) and local peritoneal infiltration (2.70). Conclusions: Contemporary local recurrence rates for sigmoid cancer are high at 12.6%. Outcomes may be improved if local recurrence is reduced at the most common sites such as the peri-anastomotic area or peritoneum. Extra-nodal CT-imaging biomarkers of local peritoneal infiltration and tumour deposits were prognostically significant on multivariate analysis in addition to pathology staging variables.